The seven tales of Trinket - Thomas, Shelley Moore (Farrar, Straus and Giroux, 2012)
"Guided by a tattered map, accompanied by Thomas the Pig Boy, and inspired by the storyteller's blood that thrums through her veins, eleven-year-old Trinket searches for the seven stories she needs to become a bard like her father, who disappeared years before"--P. [4] of cover.